Biomedical applications of natural-based polymers combined with bioactive glass nanoparticles - Leite, Álvaro J. (2017)
In recent years, the combination of natural polymers with nanoparticles has permitted the development of sophisticated and efficient bioinspired constructs. In this regard, the incorporation of bioactive glass nanoparticles (BGNPs) confers a bioactive nature to these constructs, which can then induce the formation of a bone-like apatite layer upon immersion in a physiological environment. Moreover, the incorporation of bioactive glass nanoparticles has been found to be beneficial; the constructs proved to be biocompatible, promote cell adhesion and spreading, and regulate osteogenic commitment. This review provides a summary and discussion of the composition, design, and applications of bioinspired nanocomposite constructs based on BGNPs. Examples of nanocomposite systems will be highlighted with relevance to biomedical applications. It is expected that understanding the principles and the stateof-the-art of natural nanocomposites may lead to breakthroughs in many research areas, including tissue engineering and orthopaedic devices. The challenges regarding the future translation of these nanostructured composites into clinical use are also summarized.